Correlation of Serum Magnesium Level and Blood Glucose status among Type 2 Diabetic Patients (Journal of Current and Advance Medical Research, 2021)
Background: Serum magnesium level is an important electrolytes for the maintenance of haemodynamic of the body.Objective: The purpose of the present study was to correlate the serum magnesium level and blood sugar status.Methodology: This cross sectional study was carried out in the Department of Medicine at Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh from July 2012 to December 2012. All the type 2 diabetic patients admitted in the Department of Medicine in-patient department of ShSMCH who were 18 years and above age with both sexes were included as study population and were designated as group A and non-diabetic patients were included as group B. Blood samples were drawn after an overnight fast for the measurement of fasting blood sugar and serum magnesium.Result: In this present study a total number of 60 patients were enrolled for this study after fulfilling the inclusion and exclusion criteria of which 30 patients were in group A and the rest 30 patients were in group B. The correlation coefficient of FBS and HbA1C with Serum Magnesium level was recorded. The FBS and serum magnesium was negatively correlated to each other significantly which was -0.534. The HbA1C and serum magnesium was negatively correlated to each other significantly which was -0.556.Conclusion: In conclusion the blood sugar level is inversely correlate with the serum magnesium level in type 2 diabetic patients.Journal of Current and Advance Medical Research, July 2021;8(2):106-109